The Anti-Neuroinflammatory Effect of Fuzi and Ganjiang Extraction on LPS-Induced BV2 Microglia and Its Intervention Function on Depression-Like Behavior of Cancer-Related Fatigue Model Mice - Yang, Songwei; Yang, Yantao; Chen, Cong; Wang, Huiqin; Ai, Qidi; Lin, Meiyu; Zeng, Qi; Zhang, Yi; Gao, Yan; Li, Xun; Chen, Naihong (Frontiers in Pharmacology, 2021)
The Chinese herb couple Fuzi and Ganjiang (FG) has been a classic combination of traditional Chinese medicine that is commonly used clinically in China for nearly 2000 years. Traditional Chinese medicine suggests that FG can treat various ailments, including heart failure, fatigue, gastrointestinal upset and depression. Neuroinflammation is one of the main pathogenesis of many neurodegenerative diseases in which microglia cells play a critical role in the occurrence and development of neuroinflammation. FG has been clinically proven to have an efficient therapeutic effect on depression and other neurological disorders, but its mechanism remains unknown. Cancer-related fatigue (CRF) is a serious threat to the quality of life of cancer patients and is characterized by both physical and psychological fatigue. Recent studies have found that neuroinflammation is a key inducement leading to the occurrence and development of CRF. Traditional Chinese medicine theory believes that extreme fatigue and depressive symptoms of CRF are related to Yang deficiency, and the application of Yang tonic drugs such as Fuzi and Ganjiang can relieve CRF symptoms, but the underlying mechanisms remain unknown. In order to definite whether FG can inhibit CRF depression-like behavior by suppressing neuroinflammation, we conducted a series of experimental studies in vitro and in vivo. According to the UPLC-Q-TOF/MSE results, we speculated 49 compounds in FG extraction, among which 30 compounds were derived from Fuzi and 19 compounds were derived from Ganjiang. Our research data showed that FG can effectively reduce the production of pro-inflammatory mediators IL-6, TNF-α, ROS, NO and PGE2, and suppress the expression of iNOS and COX2, which were related to the inhibition of NF-κB/activation of Nrf2/HO-1 signaling pathways. In addition, our research results revealed that FG can improve the depression-like behavior performance of CRF model mice in tail suspension test, open field test, elevated plus maze test and forced swimming test, which were associated with the inhibition of the expression of inflammatory mediators iNOS and COX2 in the prefrontal cortex and hippocampus of CRF model mice. Those research results suggested that FG has a satisfactory effect on depression-like behavior of CRF, which was related to the inhibition of neuroinflammation.